P67 Using a service evaluation to drive change and improve quality. (1st October 2013) - Newman, Peter; White, Jane; Plowman, Martin
Abstract : Introduction: Dreams Come True is a national charity providing dreams for children age 2–21 with life-threatening and life-limiting conditions. As part of our overall commitment in our 25th year to improving the quality of our dream delivery service, we have embarked on a programme of service improvement. Voluntary organisations have a key role to play in palliative care pathways and it is important that the sector is a serious partner in the drive to improve services. Aim: The starting point was an independent service evaluation designed to evaluate the views of all our stakeholders: the internal team; the key professionals who refer to our service; and most importantly the families that we serve. Methods: The study methodology used a combination of nominal group technique for parents and staff team and email survey among key referring informants. Results: This paper will focus on the lessons learned by the charity in undertaking the study and will describe the process of internal review, re-evaluation and implementation of change that has now been actioned. Such changes include ways in which we will be involving families and communications practices with professionals as well as a re-evaluation of our services to young adults in transition. Conclusion: We will describe the ongoing methods by which we will monitor the impact of those changes which we hope will achieve quality improvements to all stakeholders in our organisation. It will be of interest to other voluntary organisations supporting palliative care services nationwide especially those considering undertaking a service evaluation. It will also be of interest to children's hospitals and hospices with an interest in the professionalism and effectiveness of the service delivery of such voluntary organisations.